x . 3 + 497 = 498,02
=> 3x = 498,02 - 497
=> 3x = 1,02
=> x = 1,02 : 3
=> x = 0,34
~Study well~
#Thạc_Trân
X*3 + 497 = 498,02
X*3 = 498,02 - 497
X*3 = 1,02
X = 1,02 : 3
X = 0,34
Vậy x = 0,34
X * 3 + 497 = 498,02
X * 3 = 498,02 -497
X * 3 = 1,02
X =1,02:3
X =0,34
Vậy X=0,34
\(x\times3+497=498,02\)
\(x\times3=498,02-497\)
\(x\times3=1,02\)
\(x=1,02:3=0,34\)
X * 3 + 497 = 498,02
X * 3 = 498,02 - 497
X * 3 = 1,02
X = 1,02 : 3
X = 0,34
\(x\cdot3+497=498,02\)
\(3x=498,02-497\)
\(3x=1,02\)
\(x=1,02\text{ : }3\)
\(x=0,34\)
\(x\cdot3+497=498,02\)
\(3x=498,02-497\)
\(3x=1,02\)
\(x=1,02\text{ : }3\)
\(x=0,34\)